Pembuatan Bot Telegram Untuk Mengambil Informasi dan Jadwal Film Menggunakan PHP - Anggiat Cokrojoyo; Justinus Andjarwirawan; Agustinus Noertjahyana (Jurnal Infra, 2017)
Instant Messaging named Telegram that was launched back in August 2013 became one of the IM apps that is widely used by the people around the world. One of the features that Telegram offers is its platform of its Application Programming Interface (API). One of the APIs being the Bot API is one of the majorly used features. One of the advantages of having a Bot is its reliability to deliver data to its users since it always operates without the limit of time. Nowadays movie show times are one of the necessities, being it accessible thru the web or an app is a bit of a hassle, hence this bot is developed to reduce the effort needed to get the movie show times. All the user need to do is to send a command and the bot will reply with the necessary information. All of this is made possible by using the programming language of Hypertext preprocessor (PHP).